2015
DOI: 10.1002/pd.4708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of defined ultrasound findings of unknown significance at the second trimester fetal anomaly scan and their association with adverse pregnancy outcomes: the Welsh study of mothers and babies population‐based cohort

Abstract: ObjectiveThe aim of this article was to estimate the population prevalence of seven defined ultrasound findings of uncertain significance (‘markers’) in the second trimester and the associated risk of adverse pregnancy outcomes.MethodA prospective record‐linked cohort study of 30 078 pregnant women who had second trimester anomaly scans between July 2008 and March 2011 in Wales was conducted.ResultsThe prevalence of markers ranged from 43.7 per 1000 singleton pregnancies for cardiac echogenic foci [95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 28 publications
(39 reference statements)
1
34
0
Order By: Relevance
“…Thickened NF is defines as, thickening of the skin and the subcutaneous tissues on the posterior aspect of the fetal neck measuring 6 mm or greater before 20+6 weeks' gestation. Its prevalence is 1 to 6 per 1,000 [3]. Bromley et al [10] concluded in their retrospective study, that especially thickened NF in second trimester is the most important soft marker in the detection of Down syndrome among fetuses who have had normal first trimester sonographic screening for aneuploidy [6].…”
Section: Thickened Nuchal Foldmentioning
confidence: 99%
See 4 more Smart Citations
“…Thickened NF is defines as, thickening of the skin and the subcutaneous tissues on the posterior aspect of the fetal neck measuring 6 mm or greater before 20+6 weeks' gestation. Its prevalence is 1 to 6 per 1,000 [3]. Bromley et al [10] concluded in their retrospective study, that especially thickened NF in second trimester is the most important soft marker in the detection of Down syndrome among fetuses who have had normal first trimester sonographic screening for aneuploidy [6].…”
Section: Thickened Nuchal Foldmentioning
confidence: 99%
“…Echogenic bowel resolves spontaneously in 19.7% of cases and the association with Down syndrome reported likelihood ratio of 5.5 to 6.7 [13]. Echogenic bowel has been described as normal variant, but may be associated with congenital viral infections (particularly CMV), aneuploidy, intra-amniotic bleeding, severe uteroplacental insufficiency, meconium peritonitis, cystic fibrosis , anemia, and fetal growth restriction (FGR) [3,6,13]. Therefore, a comprehensive examination and evaluation for CMV infection is suggested, in addition to correlation with aneuploidy testing results.…”
Section: Echogenic Bowelmentioning
confidence: 99%
See 3 more Smart Citations